Energy efficiency development in German and Colombian non-energy-intensive sectors: A non-parametric analysis (2011)
This paper measures energy efficiency development in non-energy-intensive sectors (NEISs) in Germany and Colombia from a production-based theoretical framework using Data Envelopment Analysis (DEA). Using data from the German and Colombian Annual Surveys of Industries from 1998 to 2005, the analysis compares energy efficiency performances in German and Colombian NEISs at two levels of aggregation and then applies several alternative models. The results show considerable variation in energy efficiency performance in the NEISs of both countries. Comparing the results across models, it was found that in the German and Colombian NEISs, the measures of energy efficiency are similar, indicating that an appropriate combination of technical efficiency and cost minimisation are necessary to improve energy efficiency. However, energy efficiency based on cost minimisation is greater in both countries, demonstrating that energy prices in this sector are not the key variable for improving energy efficiency. This is due to the low share of energy costs, making it preferable to change other inputs rather than energy. A second-stage regression analysis reveals that in the German and Colombian NEISs, labour productivity and investments are fundamental to changes in energy efficiency. Finally, the energy efficiency measures of the DEA models show significant correlations with the traditional energy efficiency measure, indicating that energy efficiency as measured through DEA could be complementary to measures of energy intensity when analysing other key elements of energy efficiency performance in the industrial sector.